2012
DOI: 10.1158/1055-9965.epi-12-0537
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Patient Navigation for Newly Diagnosed Cancer Patients: Effects on Quality of Life

Abstract: Background Patient navigation (PN) is a promising intervention to ameliorate cancer health disparities. This study objective was to measure PN effects on cancer-specific quality of life (QOL) among newly diagnosed cancer patients. Methods A randomized, controlled trial of PN was conducted in Rochester, New York. Breast cancer and colorectal cancer patients were randomly assigned to receive a PN intervention or usual care. QOL was measured at baseline and four subsequent time points, using the validated Funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 25 publications
2
45
0
Order By: Relevance
“…Of the three existing studies examining the effects of any neighborhood deprivation metric on a cancer outcome among participants in a PN program (18, 22, 23), two reported insignificant associations (22, 23) and the other did not report the association (18). No other study has assessed the effects of CT-level measures of neighborhood deprivation, within a multilevel analytic framework or otherwise, among participants of a PN program.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the three existing studies examining the effects of any neighborhood deprivation metric on a cancer outcome among participants in a PN program (18, 22, 23), two reported insignificant associations (22, 23) and the other did not report the association (18). No other study has assessed the effects of CT-level measures of neighborhood deprivation, within a multilevel analytic framework or otherwise, among participants of a PN program.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies reported statistically insignificant associations (22, 23), while the other did not report their findings (18). Neighborhood research suggests that: 1) census tract (CTs) approximate neighborhoods better than zip codes, and 2) measures of several neighborhood constructs (e.g., racial segregation, neighborhood socioeconomic deprivation) should be considered when investigating the effects of neighborhood factors on cancer outcomes (24, 25).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…[22] Two additional randomized clinical trials evaluating patient navigator programs also failed to improve time to treatment. [23,24]…”
Section: Commentmentioning
confidence: 99%
“…Health care organizations, especially those identified as ''safety net'' providers of care, have deployed patient navigators, assigning them the tasks of identifying patients at risk of poor access, mitigating the barriers they face, and facilitating provision of care, navigating them to needed cancer care. Recent reports from the national patient navigation research program (PNRP) provide evidence of the effectiveness of this strategy to improve timely care after abnormal cancer screening (Battaglia et al, 2012;Dudley et al, 2012;Fiscella et al, 2012;Hendren et al, 2012;Hoffman et al, 2012;Markossian, Darnell, & Calhoun, 2012;Paskett et al, 2012;Raich et al, 2012;Wells et al, 2012).…”
mentioning
confidence: 99%